PERLINDUNGAN KONSUMEN MUSLIM TERHADAP PRODUK HALAL NON-SERTIFIKASI DI MARKETPLACE DIGITAL - Zainul Arifin (LPPM STAI Muhammadiyah Probolinggo, 2025)
The development of digital marketplaces has encouraged the widespread distribution of halal products, but on the other hand, it has raised issues regarding the protection of Muslim consumers due to the prevalence of non-certified halal products. This study aims to analyze the forms of legal protection for Muslim consumers in the distribution of non-certified halal products in digital marketplaces and to examine the legal responsibilities of platform providers. This study uses a normative juridical method with a legislative and conceptual approach, supported by a literature review of legislation, scientific literature, and marketplace policies. The results show that, normatively, Muslim consumer protection is regulated in the Consumer Protection Law No. 8 of 1999 and the Halal Product Guarantee Law No. 33 of 2014, but its implementation in digital marketplaces is not yet optimal. Platform providers tend to limit their responsibility as intermediaries, even though they derive economic benefits and play an active role in the transaction system. Therefore, it is necessary to strengthen the responsibility of platforms and integrate the principles of Islamic economic law in order to realize fair and sustainable protection for Muslim consumers.